2021
DOI: 10.1021/acs.jmedchem.0c02218
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Eukaryotic Elongation Factor 2 Kinase: An Update on Pharmacological Small-Molecule Compounds in Cancer

Abstract: Eukaryotic elongation factor 2 kinase (eEF2K), a member of the atypical protein kinase family of alpha-kinases, is well-known as a negative regulator of protein synthesis by phosphorylating eEF2. Notably, eEF2K functions as a key regulator of several cellular processes, leading to tumorigenesis. To date, some small-molecule compounds have been reported as potential eEF2K inhibitors in cancer drug discovery. However, an ideal targeted drug design still faces huge challenges. Alternatively, other design strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“… 281 Fluoxetine was reported to cause autophagic cell death via activating the AMPK-mTOR-ULK1 axis in TNBC cell lines. 282 , 283 Moreover, polyphyllin VI (PPVI) was a natural product with potent antitumor activity, which could regulate multiple pathways to induce autophagic cell death, such as PI3K/Akt/mTOR, MEK/ERK, and AMPK/ mTOR pathways. 284 Apigenin (APG) elicited autophagic cell death by modulating the mTOR-AMPK-ULK1 signaling pathway in GC cell lines.…”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“… 281 Fluoxetine was reported to cause autophagic cell death via activating the AMPK-mTOR-ULK1 axis in TNBC cell lines. 282 , 283 Moreover, polyphyllin VI (PPVI) was a natural product with potent antitumor activity, which could regulate multiple pathways to induce autophagic cell death, such as PI3K/Akt/mTOR, MEK/ERK, and AMPK/ mTOR pathways. 284 Apigenin (APG) elicited autophagic cell death by modulating the mTOR-AMPK-ULK1 signaling pathway in GC cell lines.…”
Section: Crucial Signaling Pathways Of Rcd Subroutines In Cancermentioning
confidence: 99%
“…13 C, 1 H-Ile-1, Met-, 2 H, 15 N-labeled CaM (IM-labeled CaM) (41) and unlabeled peEF-2K TR (35) were prepared as previously described, and the corresponding 1:1 heterodimeric complex was purified as described above. All NMR samples (unless specifically noted) were prepared in a buffer (NMR buffer) containing 20 mM Hepes (pH 7.5), 100 mM NaCl, 1.0 mM TCEP, and 5% 2 H 2 O.…”
Section: Solution Nmr Spectroscopymentioning
confidence: 99%
“…Aberrant eEF-2K function has been correlated with enhanced tumorigenesis (12), invasion, and metastasis (13). Given these properties, eEF-2K is an emerging target for the development of therapeutics against several diseases, including many cancers (14)(15)(16), and neuropathies (17), underscoring the importance of understanding its activation and regulation in mechanistic detail.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the activity of eEF2K is often found to be enhanced in many types of tumors, and the activated eEF2K in tumor cells is supposed to inhibit protein synthesis, reduces the consumption of nutrients and energy of the cells, thus assisting the tumor cells to resist adverse environments and facilitate their proliferation [ 7 , 8 ]. Consistent with this assumption, a growing number of studies have reported that inhibition of eEF2K expression or activity indeed impairs tumor cells proliferation [ 9 , 10 ]. Therefore, eEF2K is considered as a new potential target for cancer therapy, and the research and development of eEF2K inhibitors are of great clinical significance [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 87%